Controller design for a PMSG - wind turbine system - Doan, Thanh Ly (2015)
Renewable energy nowadays become more and more important to the developing of the world. Wind energy take a significant part of the renewable energy, more and more research have done in the wind energy. In this project, the student will do research on the design of a wind turbine and the control system of it. The objective of this project is designing the wind turbine and controller for the turbine. The project give the insight about how the wind turbine work and how to get the stable condition with maximum performance efficiency. The project divide into two main parts. The first part is about the organization of the wind turbine and basic operation process of each component. This part will go to details of wind turbine components. The second part of the project is designing the controller for the wind turbine. In the second part, the controller design will be tested to provide the wind turbine the best performance. All the design are simulated on Matlab.